The Quality Level of The Sociology Book from The Point of View of Supervisors and Teachers - Fahmi Yusif M. Ameen; Hamed Abdulla Salih; Adalan Latef Abdulqadr (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This study aimed to determine the level of social quality of the book from the point of view of supervisors and teachers for the year (2021-2022). Our research community is (1018) teachers of both sexes in the Center of Arbil Province; (25%)of the research sample consists of (270)teachers of both sexes;The number of basic education supervisors wa(80), (25%), supervisors of our sample consisted of (20) supervisors, To achieve the objectives of the research, the researcher used the descriptive method in this study. The final research tools consisted of (116) criteria, divided into five fields, And it was applied to the research sample (supervisors and teachers) after analyzing the questionnaire, using statistical equations, we presented the results of the research, it was found that the quality level of the ninth grade textbook is weak from the point of view of supervisors and teachers in the city of Erbil.